The problem of conveying the content of psycholinguistic terms from the category of smysl in translation (based on the works of T.V. Akhutina (Ryabova)) - K.Yu. Levin (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the major problems that arise when the key terms used in psycho- and neurolinguistics are interpreted and translated into a foreign language. The diversity and ambiguity of psycho- and neurolinguistic terms can create difficulties in, for example, the translation of the works of famous Russian psycholinguists. Here the fragments of the official translations of T.V. Akhutina's works that cover the Leontiev–Akhutina concepts going back to L.S. Vygotsky's ideas are discussed. These works focus is on the terms smysl ('sense') and znachenie ('meaning'), both of which cause substantial problems for translation. To define how the authors understand them and create an adequate translation, the theory explained in the works must be studied thoroughly and carefully. The analysis of contextual usages reveals the corresponding and controversial variants of these terms in English that occurred as a result of their translation.